1996
DOI: 10.1139/g96-081
|View full text |Cite
|
Sign up to set email alerts
|

A high density RFLP linkage map of sugar beet

Abstract: A high density sugar beet RFLP map with an average distance of 1.5 cM between markers has been constructed. The map covers 621 cM and includes 413 markers distributed over the nine linkage groups of sugar beet. The map is based on two F2 populations representing two different pairs of parents. The two sets of data were integrated into a single map using 90 markers that were common to both data sets. The quality of the map was assessed in several ways. The common markers were used to investigate how often the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Sugar beet is a true diploid member of the Amaranthaceae family and has a haploid chromosome number of nine (half that of quinoa). The total length of the several dense linkage maps reported in sugar beet range from 621 cM (Halldén et al 1996) to 815 cM (Barzen et al 1995), roughly half the size predicted for the total length (1,700 cM) of the quinoa genetic map and between 61% and 80% of the genetic map we report for quinoa (1,020 cM). Considering the probable allotetraploid origin of quinoa, a genetic map roughly twice the size of those for diploid members of the family is not unexpected.…”
Section: Linkage Analysismentioning
confidence: 47%
“…Sugar beet is a true diploid member of the Amaranthaceae family and has a haploid chromosome number of nine (half that of quinoa). The total length of the several dense linkage maps reported in sugar beet range from 621 cM (Halldén et al 1996) to 815 cM (Barzen et al 1995), roughly half the size predicted for the total length (1,700 cM) of the quinoa genetic map and between 61% and 80% of the genetic map we report for quinoa (1,020 cM). Considering the probable allotetraploid origin of quinoa, a genetic map roughly twice the size of those for diploid members of the family is not unexpected.…”
Section: Linkage Analysismentioning
confidence: 47%
“…1). Other authors have reported a non-random distribution of markers-often due to centrally located clusters-in chickpea (Winter et al 2000), sugar beet (HalldØn et al 1996) or barley (Langridge et al 1995). Sometimes the apparently random marker distribution is due to a low number of markers; when more markers are added to the map, clusters became evident, such as SSRs in soybean (Akkaya et al 1995;Cregan et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…From this examination, genotypic data from seven individuals were excluded due to an extensive amount of genotypic errors. Loci showing a skewed segregation were examined for their effects on linked markers (Hallden et al 1996).…”
Section: Linkage Analysismentioning
confidence: 99%